Correlates of verbal and physical aggression among patrons of licensed venues in Australia. (25th April 2017) - Hyder, Shannon; Coomber, Kerri; Pennay, Amy; Droste, Nicolas; Curtis, Ashlee; Mayshak, Richelle; Lam, Tina; Gilmore, William; Chikritzhs, Tanya; Miller, Peter G.
Abstract: Introduction and Aims: The current study aimed to examine the association between patron demographics and substance use, and experiences of verbal and physical aggressive incidents within the last 3 months among patrons of night‐time entertainment precincts (NEP) in Australia. Design and Methods: Patron interviews (n = 4216) were conducted around licensed venues in the NEPs of five Australian cities. Seven correlates of verbal and physical aggressive incidents were examined: gender, age, occupation, blood alcohol concentration, pre‐drinking, energy drink use and illicit drug use in the current session. Results: A total of 7.5% and 8.2% of respondents reported involvement in a verbally and physically aggressive incident in the past 3 months, respectively. Multivariate logistic regression models indicated men and people <25 years old were significantly more likely to report both verbal and physical aggressive incidents. A significant occupation effect showed lower levels of both verbal and physical aggression in managers/professionals compared with non‐office workers. The likelihood of being involved in a verbally aggressive incident significantly increased with energy drink consumption, while the likelihood of being involved in a physically aggressive incident significantly increased with blood alcohol concentration, energy drink consumption and illicit drug use. Discussion and Conclusions: This study highlights the different correlates of verbal and physical aggression within NEPs, suggesting they should be viewed as distinct types of violence, rather than points on a continuum. Major modifiable correlates with verbal and physical aggression included intoxication, energy drink consumption, and illicit drug use, suggesting the need for further interventions and policy development to address these key issues. [Hyder S, Coomber K, Pennay A, Droste N, Curtis A, Mayshak R, Lam T, Gilmore W, Chikritzhs T, Miller PG. Correlates of verbal and physical aggression among patrons of licensed venues in Australia. Drug Alcohol Rev 2018;37:6–13]